Influence of Absorption cross section of saturable absorber on Passive Q-switching laser pulse characteristics - Salih, Abdul-Kareem M. (University of Thi-Qar Journal of Science, 2019)
The absorption cross section of saturable absorber influence on passive Q-switching laser pulse behavior has been studied by numerical solution of rate equations mathematical model. We report the passive Q-switching of the 2 4 4 Cr : BeAl O  (alexandrite) laser with the yttrium silicate 2 5 4 Cr :Y SiO  (Cr :YSO) solid state saturable absorber. The study shows that the behavior pulse energy, initial value of population inversion, and the laser photon number is scaling up when the ground state absorption cross section of saturable absorber increasing, while the behavior of pulse duration is scaling down.